Induction of CD8+ T cells using heterologous prime-boost immunisation strategies. - Schneider, J; Gilbert, S; Hannan, C; Dégano, P; Prieur, E; Sheu, E; Plebanski, M; Hill, A (1999)
One of the current challenges in vaccine design is the development of antigen delivery systems or vaccination strategies that induce high protective levels of CD8+ T cells. These cells are crucial for protection against certain tumours and intracellular pathogens such as the liver-stage parasite of malaria. A liver-stage malaria vaccine should therefore include CD8+ T-cell-inducing components. This review provides an overview of prime-boost immunisation strategies that result in protective CD8+ T-cell responses against malaria with an emphasis on work from our laboratory. Possible mechanisms explaining why heterologous prime-boost strategies, in particular boosting with replication-impaired recombinant poxviruses, are so effective are discussed.